The effect of housework on wages in Germany: no impact at all - Boris Hirsch; Thorsten Konietzko (Journal for Labour Market Research, 2013)
This paper presents evidence on the impact of hours spent on housework activities on individuals' wages for Germany using data from both the German Socio-Economic Panel and the German Time Use Survey. In contrast to most of the international literature, we find no negative effect of housework on wages. This holds for men and women, for married and single individuals, and for part-time and full-time workers both in West and East Germany. Our insights do not change when we distinguish different types of housework activities or address the endogeneity of housework in our wage regressions by using instrumental variables estimators.
Keywords: J16; J31; J22; 330; Hausarbeit; Einkommenseffekte; Lohnhöhe; geschlechtsspezifische Faktoren; Zeitbudget; Ehepartner; allein Stehende; Vollzeitarbeit; Teilzeitarbeit; Lohnunterschied; erwerbstätige Frauen; erwerbstätige Männer